If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -2) + 9 = 7(1 + -1x) Reorder the terms: 5(-2 + x) + 9 = 7(1 + -1x) (-2 * 5 + x * 5) + 9 = 7(1 + -1x) (-10 + 5x) + 9 = 7(1 + -1x) Reorder the terms: -10 + 9 + 5x = 7(1 + -1x) Combine like terms: -10 + 9 = -1 -1 + 5x = 7(1 + -1x) -1 + 5x = (1 * 7 + -1x * 7) -1 + 5x = (7 + -7x) Solving -1 + 5x = 7 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -1 + 5x + 7x = 7 + -7x + 7x Combine like terms: 5x + 7x = 12x -1 + 12x = 7 + -7x + 7x Combine like terms: -7x + 7x = 0 -1 + 12x = 7 + 0 -1 + 12x = 7 Add '1' to each side of the equation. -1 + 1 + 12x = 7 + 1 Combine like terms: -1 + 1 = 0 0 + 12x = 7 + 1 12x = 7 + 1 Combine like terms: 7 + 1 = 8 12x = 8 Divide each side by '12'. x = 0.6666666667 Simplifying x = 0.6666666667
| F(x)=-6x^2-2x-9 | | -48x+17=3x-2 | | -x^2+2x+40=0 | | p=5p-17 | | F(x)=6x^2-2x-9 | | 3x14/15 | | (1/3)x=100 | | 2r^2-24r=0 | | 100=1/3x | | D=7.5m | | 5(2x-1)=9x+x+5 | | 4x-4.7=35 | | .5z+30=z | | 1x11/4 | | C-100/-8=0 | | T=n+14.50 | | 5y+6=-12y+62 | | 3x/4/10 | | p=5a-17 | | 24.039+6.016= | | x/3=2.13 | | T=n+7.25 | | H-62/5=5 | | 9=7b+7 | | 2y+9(8-4)=52 | | 7y+6=46+3y | | .45/x=2.05 | | 4e-16+5e=28 | | 40+5x=125 | | 10.358+2.416= | | 2k+7+8x=13 | | 10+x(x)=144 |